Student’s Attitude and Challenges toward Teaching Practicum Programme (PPL) in Junior High School - Nova Sri Inarsih; Sastika Seli; Dewi Syafitri (EDULIA: English Education, Linguistic and Art Journal, 2021)
This study aims to describe the attitudes and challenges of students towards the teaching practicum program (PPL) of STKIP-PGRI Lubuklinggau in Junior High School. The research method used is descriptive qualitative research. The research subjects were 16 respondents who were selected by purposive sampling. In collecting data, researchers used interviews and questionnaires. The results showed that many respondents had the most positive attitudes towards the affective and behavioral components. However, the component with the lowest teacher candidate teacher attitudes is the cognitive component. In terms of challenges for prospective teachers, most respondents (37.5%) rated field workload as a challenge, while the least field of supervision was faced by respondents during PPL (6.25%). In conclusion, the analysis of findings related to the attitudes of prospective STKIP-PGRI Lubuklinggau teachers in Junior High Schools is an almost positive attitude. Keywords: Attitudes, Challenges, Pre-Service Teachers, Teaching Practicum Program